AN ANALYSIS OF QUESTIONING MODIFICATIONS EMPLOYED BY TEACHER IN EFL CLASSES OF GRADE 11 OF SMA NEGERI 2 BANJAR - ., I PT AGUS KUSUMA W; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Luh Diah Surya Adnyani, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This present study aimed at analyzing the frequency of teacher asking questions in EFL classes of grade 11 of SMAN 2 Banjar, describing the types of questioning modifications employed by the teacher, and finding out the reasons for the teacher to modify the questions. The present study was a descriptive-qualitative study with an English teacher as the subject. In collecting data, four kinds of instrument were used, namely, the researcher, video recorder, audio recorder, and observation sheets. The video recorder and observation sheets were used to get data in form of questions and questions modification employed by the teacher. In addition, the audio recorder was used to get data in form of reasons for teacher to modify the questions. The result of this study revealed that the English teacher employed three types of question with difference frequencies of occurrence. They were procedural question (49%), convergent questions (31%), and divergent questions (20%). It was also revealed that the teacher employed seven types of question modification, namely, repeating or rephrasing (27.0%), narrowing by means of clues (11.0%), rephrasing with alternative or â€œor-choiceâ€ (2.5%), wait-time (13.5%), translating the questions into L1 (43.0%), translating the question into English (1.0%), and code mixing (2.0%). In addition, the reason for the teacher to modify the questions was dominantly to help the students understand the question.keyword : English language teaching, questions, question modification